2015
DOI: 10.1124/jpet.115.228205
|View full text |Cite
|
Sign up to set email alerts
|

Encenicline, an  7 Nicotinic Acetylcholine Receptor Partial Agonist, Reduces Immune Cell Infiltration in the Colon and Improves Experimental Colitis in Mice

Abstract: The a7 pentamer nicotinic acetylcholine receptors (nAChRs) are a target in transduction of anti-inflammatory signals from the central nervous system to the gastrointestinal (GI) tract. The aim of this study was to investigate the anti-inflammatory action of the novel a7 nAChR partial agonist encenicline and to determine the mechanism underlying its activity. Anti-inflammatory activity of encenicline was evaluated using trinitrobenzenesulfonic acid (TNBS)-and dextran sulfate sodium (DSS)-induced models of colit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 41 publications
(56 reference statements)
1
26
0
Order By: Relevance
“…Studies investigating the cellular and molecular mechanisms of spleen involvement in the cholinergic anti-inflammatory responses in experimental colitis have focused on dendritic cells and their ability to prime T cells (Munyaka et al, 2014) and on the presence of specific subtypes of T cells in the submucosa of the colon (Salaga et al, 2016). This work demonstrated that in vivo stimulation of α7nAChRs on dendritic cells via central vagal stimulation decreased release of Th1/Th17 pro-inflammatory cytokines from these cells in vitro and impaired their ability to prime T cells.…”
Section: Vagal Anti-inflammatory Pathway To the Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating the cellular and molecular mechanisms of spleen involvement in the cholinergic anti-inflammatory responses in experimental colitis have focused on dendritic cells and their ability to prime T cells (Munyaka et al, 2014) and on the presence of specific subtypes of T cells in the submucosa of the colon (Salaga et al, 2016). This work demonstrated that in vivo stimulation of α7nAChRs on dendritic cells via central vagal stimulation decreased release of Th1/Th17 pro-inflammatory cytokines from these cells in vitro and impaired their ability to prime T cells.…”
Section: Vagal Anti-inflammatory Pathway To the Gutmentioning
confidence: 99%
“…It remains unclear how anti-inflammatory signals are transferred to the gut, but it most likely involves trafficking of cells from the spleen. Recent work has in fact demonstrated that treatment with encenicline, a partial agonist at the α7nAChR, reduced the infiltration of macrophages, neutrophils and B cells into the mucosa and submucosa of the colon in TNBS induced colitis in mice (Salaga et al, 2016). Furthermore, while the total number of T cells infiltrating the colon was unaffected by encenicline, the drug did reduce the abundance of FoxP3 + IL-17A + T cells, which have a pro-inflammatory role in IBD.…”
Section: Vagal Anti-inflammatory Pathway To the Gutmentioning
confidence: 99%
“…To combat this—several selective α7nAChR agonists have been developed and tested on animal models of DSS‐induced colitis as well as models of experimental endotoxemia in healthy human volunteers. These early pre‐clinical studies have yielded conflicting results to date, with results likely hampered by the pharmacodynamic and pharmacokinetic properties of these compounds, as optimum administration routes, dosages and translatability from animal to human models are still being investigated . Effects on disease activity in patients with IBD using vagal tone modulation by other means such as controlled slow deep breathing, chanting meditation and prescribed exercise programs are yet to be reported.…”
Section: Therapeutic Modulation Of Parasympathetic Tonementioning
confidence: 99%
“…6x) by evaporation of dichloromethane at ca. 37°C [36][37][38][39][40]. After concentration the samples were subjected to GC-MS analysis on a Shimadzu QP2010 apparatus [41][42][43][44][45][46].…”
Section: Methodsmentioning
confidence: 99%